Unusual Histomorphometric Changes in the Iliac Crest in Ovariectomized and Sham-operated Ewes - Turner, A. S.; Villanueva, A. R.; Alvis, M. R.; Aberman, H. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
A large animal model to study cancellous bone loss and the effect of various therapeutic agents following oestrogen deficiency-related bone loss is needed. Following double fluorochrome labeling at the time of surgery, six and 12 months later, static and dynamic histomorphometry was performed on undecalcified sections of the iliac crests of 16 mature (4 to 5-yearold) ewes following ovariectomy (OVX; n = 8) or sham-operation (Sham; n = 8). We found a slight decrease in bone mass associated with oestrogen deficiency as indicated by a statistically significant increase in trabecular separation (Tb.Sp: +14%, p <0.05) and decrease in wall thickness (W.Th: -10%, p <0.05) in the OVX group. However, at six months, we saw evidence of complete cessation of bone formation in both OVX and Sham animals. At that time there was a statistically significant (p <0.05) decline in the following parameters in both the Sham and OVX animals respectively: osteoid surface (OS: -79%, -77%), osteoid thickness (O.Th: -40%, -30%), flat osteoblasts (Fl.Ob.S: -87%, -94%), cuboidal osteoblasts (Cu.Ob.S: -88%, -65%), osteoid surface as a percentage of the total cancellous bone perimeter (OS/BS: -82%, -80%), osteoblast surface as a percentage of total cancellous bone surface (Ob.S/BS: -94%, -77%), mineralizing surface as a percentage of double labels plus half single labels (MS/OS: -44%, -42%), osteoid volume as a percentage of total area of mineralized bone plus osteoid (OV/TV: -88%, -88%), osteoid as a percentage of mineralized bone (OV/BV: -87%, -86%), osteoid maturation time (Omt: -27%, -35%), bone formation rate, surface referent (BFR/BS: -90%, -87%), bone formation rate, volume referent (BFR/BV: -89%, -86%), and bone formation rate, tissue referent (BFR/TV: -91%, -88%). The data was compared to static and dynamic histomorphometry of three intact ewes (similar age, breed, source) whose biopsies were taken two months after the second biopsies in the present study. The data indicate that there is a slight loss of trabecular bone following OVX but we are unable to explain the dramatic depression of bone turnover with little change in bone resorption. The data resembles the response seen when sheep are given daily doses of methylprednisolone. We speculate that this phenomenon may be a response to endogenous corticosteroid release in a response to stresses of transport, and surgery. A seasonal effect may be another explanation fro these changes, whereas dietary alteration (e. g. poisonous plants), hormonal changes or response to changes in physical activity are unlikely causes.A large animal model to study cancellous bone loss and effect of various therapeutic agents following oestrogen deficiency – related bone loss is needed. Following double fluorochrome labeling at the time of surgery, six and 12 months later, static and dynamic histomorphome-try was performed on undecal-cified sections of the iliac crests of 16 mature (4 to 5-year-old) ewes following ovariectomy (OVX; n = 8) or sham-operation (Sham; n = 8). A slight decrease in bone mass associated with oestrogen deficiency was seen but there was also evidence of complete cessation of bone formation in both OVX and Sham animals. The data resembles the responses seen when sheep are given daily doses of methylpednisolone and may be a response to endogenous corticosteroid release. A seasonal effect may be another explanation for these changes, whereas dietary alteration (e. g. poisonous plants), hormonal changes or response to changes in physical activity are unlikely causes.
Keywords: Ovariectomy; bone histomorphometry; ewe; bone volume; bone turnover